BEOWULF AND THE PERMUTATIONS OF A GERMANIC LEGEND: THE INCARNATIONS OF INGELD ACROSS GERMANIC LITERATURE AND CULTURE - Currie, Edward (2018)
This dissertation examines the varying uses and contexts of the legend of Ingeld, a key figure across a range of Germanic literature and culture whose manipulation by the poet of Beowulf remains one of the most cryptic yet crucial allusions in that poem. His appearance in Old English verse is perhaps most familiar to scholars, but he is also represented significantly in Saxo Grammaticus’s Gesta Danorum (“Deeds of the Danes”), and in Snorri Sturluson’s Ynglingasaga (“Saga of the Ynglings”). No sustained evaluation of this figure’s varying facets or crucial role in displaying the different agendas of each of these works has yet appeared. The thematic innovations of authors on traditional narratives about Ingeld, who is a young ruler influenced by an old counselor, not only reveal authors’ rhetorical purposes, but also betray their ideological positions. Studying the narratives of Ingeld offers us the opportunity to puzzle out the variety and sophistication of medieval authors’ transformations and adaptations of legendary narratives according to various value systems and political intentions. Chapter 1 analyzes how the Beowulf poet took a traditional tale of Ingeld and put it to new use in order to educate his audience; we also investigate the influence of the author’s religious views on the representation of martial heroism. Proceeding chronologically, chapter 2 examines how the Danish author of the Gesta Danorum, Saxo Grammaticus, restores glory to martial heroism in order to create an ancient past of grand Danish warriors that never existed. His most ambitious episode features the old counselor Starcatherus converting the young King Ingellus to heroism in order to protect the Danish throne from the foreign Saxon threat: unlike the Beowulf poet, who writes chiefly in the exemplary mode, Saxo makes patriotism the principal value of his work. Chapter 3 considers the representations of Ingeld and Starkad in Iceland, where the two appear separately. Ingeld is changed into an explicitly “ill-advised” politician ...